Elliptical Birefringent Rib‐Channel Chirowaveguides for Quasicircularly Polarized Light Applications in Integrated Photonics. Issue 7 (7th March 2022) - Sahib, Hoshang; Gassenq, Alban; Bensalah-Ledoux, Amina; Baguenard, Bruno; Guy, Laure; Guy, Stephan
Abstract : Polarization in photonic‐integrated circuits (PICs) is governed by transverse electric (TE) and magnetic (TM) polarizations due to the planar structure of the chips. Therefore, all states of polarization (SOPs) other than TE and TM, in particular circular polarization, cannot be routed without modification across the chips. Herein, the realization of rib‐channel chirowaveguides supporting elliptically polarized guided modes by combining linear and circular birefringences as predicted by the coupled mode approach is shown. The sol–gel process and the imprint technique to make channel chirowaveguides with different sizes and consequently modulate ellipticity of the eigenmodes from linear to quasicircular are used. Circularly polarized light propagates therefore with a low polarization beating and in particular without handedness inversion. These results open the field of application of PICs to all domains where circularly polarized light is relevant. Abstract : Circular and elliptical polarizations in photonic integrated circuits are difficult to handle due to polarization beating from transverse electric/magnetic polarization decomposition. Engineering a chiral material with a dedicated cross‐sectional shape allows realization of chirowaveguides supporting elliptically polarized guided modes. The conservation of quasi‐circular polarization is demonstrated in channel chirowaveguides fabricated by sol‐gel process and PDMS imprint technique.